FOOD SAFETY IMPLEMENTATION OF BONELESS SIGANIDS (Siganus puellus) TECHNOLOGY - Castro, Charena J. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2023)
Food safety is vital in any fish processing activities. This paper aimed to determine the gender role on how food safety be implemented in boneless siganid processing activities. This study utilized the experimental and descriptive methods of research employing the process of coconut water treated boneless danggit production observing the good manufacturing practices (GMP) and hazard analysis critical control point (HACCP) protocol after analyzing the microbial content of boneless danggit in Taboan market. The study revealed that the samples of the top three best seller dried danggit, pusit and mangsi had bacterial total plate count of 1.0 x 104 cfu/g, 2.5 x 104 cfu/g and 5.0 x 104 cfu/g, respectively; mold count of 2.3 x 101 cfu/g, 2.0 x 101 cfu/g, and 1.5 x 101 cfu/g. The Staphylococcus aureus count of 30, 50 and 100 cfu/g sample for dried danggit, pusit and mangsi, were within the acceptable standards of Bureau of Food and Drug Administration. The pH level of dried fish samples was within 6.1 to 6.5, while the water activity of the dried products is 0.98 based on Lupin’s water activity (Aw) mathematical calculation. The experimental process of coconut water treated boneless danggit had 3.3 x 103 cfu/g which had lower count compared to the commercial samples. The process had been disseminated to the five groups of Bantayan, Cebu, Philippines fisherfolks who engaged in boneless siganids industry emphasizing the GMP and HACCP protocol of processing. Out of 50 fisherfolks engaged in boneless siganid industry, 70% are female with age bracket of 35-55 years old. Most of the female responsibilities in the industry are filleting, salting, drying and packing the dried products, while male did the fishing, chilling of raw siganids and transporting of finished products. The food safety was integrated in the salting and drying processes by using chilled coconut water and drying cabinet instead of exposing the product under the heat of the sun since proliferation of flies couldn’t be controlled. Continuing food safety and HACCP integration to all boneless siganid industry of the island is recommended.